Mini review: Persister cell control strategies - Hashemi, Mohamad Javad; Dhaouadi Khattab, Yousr; Ren, Dacheng (Frontiers in Pharmacology, 2025)
Bacterial persisters are growth-arrested cells with low metabolic activities, but have no genetic mutations compared to their parental cells. The dormant nature of persister cells enables them to tolerate high doses of conventional antibiotics and restart growth after the antibiotic is withdrawn, posing an important challenge to infection control. To promote more research in this important area, we present a concise review of current persister control strategies and discuss future opportunities.